Right-peripheral elements and text types in Ancient Greek (Minerva, 2018)
The paper studies the functions conveyed by the right-peripheral elements (RPE) in ancient Greek. It analyses whether text-types have any influence on the functions expressed by them. The conclusion is that there are interesting variations: commentary and specification functions are present in all of the texts analysed. Nonetheless, not all of these texts present functions related with the interaction of speaker and hearer.
Keywords: right periphery; pragmatics; text types